DEVELOPING ENGLISH WRITING MATERIALS OF PROCEDURE TEXT FOR STUDENTS GRADE 11 OF CULINARY PROGRAM AT SMK NEGERI 10 MEDAN - Hafiza Namira; Masitowarni Siregar; Anni Holila Pulungan (Universitas Negeri Medan, 2019)
Students’ worksheet, as one of learning tools that is used to involve the students to work actively during teaching and learning process, should be developed based on the students’ need. Students’ worksheet with scientific approach in listening skill has not applied. A good student’s worksheet must be satisfied criteria of valid, practical and effective. This research is a developmental research using Research and Development (RnD). It has been conducted on 35 students of SMK Negeri 10 Medan grade X for Multimedia Program. In this study, data obtained from Curriculum syllabus analysis, students’ need analysis and results of validation. Students’ need analysis was done to analyze the students’ perception about the previous learning materials and to know what kind of learning material they need. All of student answer the questionnaire in students’ worksheet in listening skill. From their answers are summarized into questions and answers for students’ worksheet, especially in the listening activity. Keywords: Students’ worksheet, scientific approach, listening skill.